Attitude's Mediating Role in Electric Motorcycle Purchase: Perceptions, Environment, and Incentives in Jakarta - Akbar, Muhamad Iqbal; UTama, Andyan Pradipta (International Journal of Indonesian Business Review, 2025)
Purpose – This study aims to analyze the determinants of electric motorcycle purchase intention, focusing on the mediating role of consumer attitude. Specifically, it investigates the influence of Perceived Usefulness, Perceived Ease of Use, Environmental Concern, and Government Incentives on Purchase Intention, with Attitude serving as the mediating variable. Methodology – A quantitative approach was employed, with data collected through online questionnaires from 176 respondents residing in Jakarta and its surrounding areas. The majority of respondents were young adults, held Bachelor's degrees, and worked as private employees. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Findings – The results indicate that Perceived Usefulness, Perceived Ease of Use, and Environmental Concern positively and significantly influenced Attitude. Attitude also positively and significantly influenced Purchase Intention. Regarding direct effects, Perceived Usefulness and Government Incentives significantly influenced Purchase Intention, while Perceived Ease of Use and Environmental Concern did not. Furthermore, mediation analysis revealed that Attitude partially mediated the relationship between Perceived Usefulness and Purchase Intention. Attitude fully mediated the relationships between Perceived Ease of Use and Purchase Intention, as well as Environmental Concern and Purchase Intention. However, Attitude did not mediate the relationship between Government Incentives and Purchase Intention, suggesting that incentives primarily function as direct, pragmatic drivers. Novelty – This research contributes theoretically by confirming the central role of Attitude in the consumer behavior model for adopting eco-friendly technology. It also provides practical implications for government and manufacturers in formulating effective strategies to enhance electric motorcycle purchase intention.